2020
DOI: 10.1523/jneurosci.0940-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

4E-BP1 Protects Neurons from Misfolded Protein Stress and Parkinson's Disease Toxicity by Inducing the Mitochondrial Unfolded Protein Response

Abstract: Decline of protein quality control in neurons contributes to age-related neurodegenerative disorders caused by misfolded proteins. 4E-BP1 is a key node in the regulation of protein synthesis, as activated 4E-BP1 represses global protein translation. Overexpression of 4E-BP1 mediates the benefits of dietary restriction and can counter metabolic stress, and 4E-BP1 disinhibition on mTORC1 repression may be neuroprotective; however, whether 4E-BP1 overexpression is neuroprotective in mammalian neurons is yet to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…To our knowledge, the consequences of overexpression of these proteins in SCs has not been explored. However, overexpression of 4E-BP1 is neuroprotective in neuronal cultures treated with brefeldin A, rotenone, maneb, or paraquat ( Dastidar et al, 2020 ), compounds known to affect mitochondrial function ( Drechsel and Patel, 2008 ). Importantly, these neuroprotective effects are believed to be mediated by activation of the mtUPR downstream of 4E-BP1 ( Dastidar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the consequences of overexpression of these proteins in SCs has not been explored. However, overexpression of 4E-BP1 is neuroprotective in neuronal cultures treated with brefeldin A, rotenone, maneb, or paraquat ( Dastidar et al, 2020 ), compounds known to affect mitochondrial function ( Drechsel and Patel, 2008 ). Importantly, these neuroprotective effects are believed to be mediated by activation of the mtUPR downstream of 4E-BP1 ( Dastidar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, overexpression of 4E-BP1 is neuroprotective in neuronal cultures treated with brefeldin A, rotenone, maneb, or paraquat ( Dastidar et al, 2020 ), compounds known to affect mitochondrial function ( Drechsel and Patel, 2008 ). Importantly, these neuroprotective effects are believed to be mediated by activation of the mtUPR downstream of 4E-BP1 ( Dastidar et al, 2020 ). Moreover, upregulation of 4E-BP1 is protective in pancreatic islet cells in a context of ER stress in different models of diabetes ( Yamaguchi et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, antibiotics that inhibit mitochondrial protein synthesis, namely doxycycline and chloramphenicol, have been shown to upregulate the expression of ATF5dependent UPR mt genes and extend lifespan in C. elegans (Houtkooper et al, 2013). Furthermore, repression of protein synthesis can also protect against Aβ and α-syn aggregation and neurotoxicity by inducing the expression of UPR mt -linked genes (Sorrentino et al, 2017;Dastidar et al, 2020). Second, drugs that increase the concentration of NAD + , or mimic this effect, appear to activate the ATF5-UPR mt and SIRT3-UPR mt to extend lifespan and protect against NDD-related cellular and organismal decline in various model systems (Belenky et al, 2007;Houtkooper et al, 2013;Mouchiroud et al, 2013;Regitz et al, 2016;Lehmann et al, 2017;Sorrentino et al, 2017).…”
Section: Therapeutics Targeting the Mitochondrial Unfolded Protein Re...mentioning
confidence: 99%
“…Mitochondrial diseases [60,64,73] Parkinson's disease [93][94][95][96]148] Alzheimer's disease [105][106][107][108][109] Huntington's disease [115] Amyotrophic lateral sclerosis [121][122][123][124] Heart diseases [132] Aging [139][140][141][142] Cancer [157,160] Author Contributions:…”
Section: Condition Related Studiesmentioning
confidence: 99%
“…Ginseng protein protected against neurodegeneration by inducing UPR mt in a PINK1 fly model of PD [ 94 ]. Dastidar SG et al demonstrated that activation of 4E-BP1 correlates with UPR mt induction, which reduces PD associated neurotoxicity in mouse neurons [ 95 ]. In fact, mutant LRRK2 G2019S , the most common PD-causing allele in humans, results in reduced 4E-BP1 function and may contribute to PD pathogenesis by UPR mt underactivation [ 96 ].…”
Section: Neurodegenerationmentioning
confidence: 99%